Selhání primární léčby dislokované suprakondylické zlomeniny humeru u dětí - Urbášek, Karel; Plánka, Ladislav (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2014)
PURPOSE OF THE STUDY: The aim of the study was to retrospectively evaluate the treatment outcomes of displaced supracondylar humerus fractures, including potential complications, in children treated at the Department of Paediatric General Surgery, Orthopaedics and Trauma Surgery of the Faculty of Medicine in Brno between 2000 and 2011. MATERIAL AND METHODS: The study comprised 564 children, 321 (57%) boys and 243 (43%) girls, who were allocated to two groups according to the method of primary treatment. The average age at the time of injury was 6.8 years (range, 1 to 16). In group 1, all 499 patients were indicated for primary closed reduction and percutaneous osteosynthesis with crossed K-wires under general anaesthesia. In group 2, all 65 patients underwent closed reduction under general anaesthesia and immobilisation in a high plaster cast. The per cent failure of primary treatment requiring either repeat surgery or a change in treatment strategy was evaluated. The duration of follow-up ranged from 14 to 150 months. RESULTS: Open fractures were recorded in eight (1.4%) patients. Twenty-five (4.4%) children had further injury to the ipsilateral limb. Three (0.5%) patients underwent open reduction because it was not possible to achieve adequate reduction by the closed method. In group 1, percutaneous osteosynthesis was performed using two crossed K-wires in 484, three K-wires in 13 and four K-wires in two patients. Re-displacement of fracture fragments requiring repeat reduction and percutaneous osteosynthesis occurred in 10 (2%) patients. One patient had two re-operations. In group 2, the primary treatment failed in 13 (20%) children who needed repeat reduction and conversion to percutaneous osteosynthesis. The difference in the occurrence of failure between the two groups was significant (p<0.001). Nerve injury was recorded in 92 patients (16.3% of all children and 18% of those treated with percutaneous osteosynthesis). Neurosurgical intervention was necessary for injury to the ulnar nerve in five patients and to the radial nerve in one patient. Three children had vascular injury requiring vascular surgery. Two patients underwent corrective osteotomy of the distal humerus for cubitus varus deformity. Volkmann's contracture as a complication was not recorded. DISCUSSION: Minimally displaced fractures can be treated by closed reduction and plaster cast immobilisation but this method fails in up to 20% of cases. A poor result is related to the extent of dorsal displacement before reduction; on the other hand, degrees of flexion in a plaster cast have no effect. The most frequent technical errors resulting in re-displacement after primary osteosynthesis include incomplete reduction and primary fixation in displacement, or failure of both K-wires to pass through the opposite cortex or to fix both fragments firmly. A K-wire diameter smaller than 1.6 mm may also be a reason for failure. The main problem of the method of two crossed K-wires is a frequent injury to the ulnar nerve. CONCLUSIONS: Supracondylar humerus fracture is, regardless of advancements in therapy, an injury with an uncertain treatment outcome and a high percentage of complications. Since primary osteosynthesis failed in 20% of the patients treated by simple reduction under general anaesthesia and plaster cast immobilisation, for the patients requiring fracture reduction under general anaesthesia, the authors recommend one-stage primary treatment including K-wire transfixation. Re-displacement after primary osteosynthesis was always due to a technical error during the surgical procedure and can, therefore, be avoided by a precise operative technique.
Keywords: Fractures, Malunited; Male; špatně zhojené fraktury; Treatment Outcome; vnitřní fixace fraktury; retrospektivní studie; Radial Nerve; osteotomie; Osteotomy; Humans; poranění cév; Vascular Surgical Procedures; Czech Republic; Česká republika; mužské pohlaví; reoperace; neurochirurgické výkony; Female; následné studie; Humeral Fractures; Peripheral Nerve Injuries; Reoperation; ženské pohlaví; Retrospective Studies; Neurosurgical Procedures; Follow-Up Studies; interní fixátory; Postoperative Complications; Fracture Fixation, Internal; výkony cévní chirurgie; Internal Fixators; fraktury humeru; poranění periferního nervu; Vascular System Injuries; lidé; dítě; pooperační komplikace; Child; nervus radialis; výsledek terapie